Analysis on Indonesian Sustainable Palm Oil (ISPO):A Qualitative Assessment the Success Factors for ISPO - Dina Harsono; M. Achmad Chozin; Anas M. Fauzi (Jurnal Manajemen & Agribisnis, 2012)
ISPO (Indonesian Sustainable Palm Oil) serves as the baseline of sustainability standards for palm oil industry and is expected to improve the competitive advantage of Indonesian palm oil industry. ISPO was introduced by the government in March 2011 and currently most of plantations are in process of applying ISPO. The objective of this research is to analyze success factors affecting implementation of ISPO. Using qualitative method of in-depth interview on 20 selected experts representing actors mapped in the value chain of palm oil industry. The results depicted that; very little companies apply sustainable principles hence ISPO is needed for industrial standards, success factors affecting ISPO implementation, and necessary conditions for ISPO implementation. SWOT technique resulting 8 recommended strategies to be applied for ISPO implementation. Acknowledging ISPO applies to upstream industry (plantations and mills) only, managerial implication for this research is the need to develop of a grand master plan for Indonesian palm oil Industry by developing integrated policies complementing ISPO aiming for sustainability, growing and developing downstream industry to add value to CPO product, and for upstream industry to be developed by farmers and cooperatives while big investors to develop mills and downstream industry.Keywords: Palm Oil, ISPO, Sustainable Certification, Success Factors, Qualitative